An analytical study of Cebuano-induced errors in the use of voice as verbal category in English with suggested instructional aids - Patangan, Ma. Elouisa A. ([Quezon City s.n.], 1973)
A structural contrast of voice as verbal category in both English and Cebuano is provided in this paper. It categorizes Cebuano-induced errors in using voice in English verbs for the purpose of locating problem spots on which to base sound instructional materials.
Thesis (M.A.T.English)--University of the Philippines.
Keywords: English languge -- Verb -- Study and teaching; Cebuano language -- Verb